2022
DOI: 10.1038/s41431-022-01058-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ethics of genetic prioritisation for COVID-19 vaccines

Abstract: There is evidence to suggest that host genomic factors may account for disease response variability in COVID-19 infection. In this paper, we consider if and how host genomics should influence decisions about vaccine allocation. Three potential host genetic factors are explored: vulnerability to infection, resistance to infection, and increased infectivity. We argue for the prioritisation of the genetically vulnerable in vaccination schemes, and evaluate the potential for ethical de-prioritisation of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This strategy will reduce the burden on the availability of vaccines within resource-limited areas. This strategy has been recently suggested by Bruce and Johnson (2022), who showed that individuals with genetic risk factors should be prioritized for vaccination drives [75].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy will reduce the burden on the availability of vaccines within resource-limited areas. This strategy has been recently suggested by Bruce and Johnson (2022), who showed that individuals with genetic risk factors should be prioritized for vaccination drives [75].…”
Section: Discussionmentioning
confidence: 99%
“…In a paradigm shift, prophylactic vaccines containing the SARS-CoV-2 virus spike surface protein gene delivered in both DNA and mRNA forms were approved in record time for emergency use [ 112 , 113 ]. The use of these methodologies has brought about several ethical questions regarding both their use and the speed of their approval [ 114 , 115 ]. However, the approach of nucleic acids as a vaccine for infectious diseases is not a novelty unique to COVID-19, since, before 2020, the use of DNA for developing therapies or prophylaxes for humans was addressed [ 116 ], such as vaccines for dengue [ 117 ], hepatitis [ 118 ], malaria [ 119 ], Chagas disease [ 120 ], and schistosomiasis [ 121 ].…”
Section: Theranostic Nucleotidementioning
confidence: 99%
“…While media are taking care mainly of the viral genome, the host genome is the real discriminant between severe COVID-19 and asymptomatic SARS-CoV-2 infection. Therefore, while COVID-19 is representing a challenge for the health systems and society, it is the first real opportunity to move forward on understanding mechanisms and new rules useful in clinical practice of complex disorders, as described in the papers of this issue [1][2][3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…explore how host genetics may impact decisions about vaccine administration. As host genetic factors influence vulnerability, as well as resistance to infection, they evaluate the prioritisation of genetic vulnerability in vaccination schemes, and the potential for ethical de-prioritisation for resistors [7]. Another unexplored area about vaccines is related to the socalled "more common" rare disease with impact on lung function such as α-1 antitrypsin (A1AT) deficiency (AATD) [8].…”
mentioning
confidence: 99%